Educators in Search of the Fine Line between Use and Misuse of New Technologies - Dana Hanesova; Andrea Nelson; Ken Badley (Communications - Scientific letters of the University of Zilina, 2017)
The currently youngest generation of learners has been massively influenced by ubiquitous technology. Due to their developmental cognitive and moral immaturity, decisions about the intensity of their use of ICT lies on the shoulders of their educators who have grown up in a different, pre-globalized world. These adults are often not aware of their insufficiently substantiated approach to their use of ICT in teaching. To become sufficiently informed requires considering various viewpoints, ranging on a continuum from techno-sceptic to techno-utopian. Responsible decisions about the ethical use of ICT can be reached only after considering the issues of the power of ICT as well as the need of coherent research of young learners’ needs and teachers’ capabilities. The authors share the results of research in various countries. They propose some solutions to this ethical problem, ones they consider suited to reflexive education.